The Impact of the Merdeka Curriculum on the Creativity of Fifth Grade Students in Social Studies (IPAS) Learning at SDN 21 Pekanbaru - Febriani, Kiki; Mustika, Dea (The Future of Education Journal, 2024)
Before the implementation of the independent curriculum, according to teachers, student creativity, especially in science subjects, tended to be limited, because learning focused on understanding basic concepts and working on questions, learning was also more teacher-centered where students received more information from teachers, which caused student creativity to tend to be invisible. The aim of this research is to determine the impact of independence on the creativity of class V students in learning science at SDN 21 Pekanbaru. The research that will be used in this research is quantitative research with an ex-post facto design. In the context of this research, the population consists of all class V students at SDN 21 Pekanbaru with a sample of 71 determined using a saturated sampling technique. Data collection techniques in this research used observation and questionnaires and the research instrument was a questionnaire sheet. Hypothesis testing in this research involves a Simple Linear Regression test. Based on research findings from simple linear regression analysis, a significance value of 0.497 was found which was smaller than the probability of 0.005, and a t-count value of 0.716 which was greater than the t table of 0.514. So it was concluded that the Merdeka Curriculum had a positive impact on student creativity in class V science learning at SDN 21 Pekanbaru.